State Responsibility for "Targeted Sanctions". (2019) - Tzanakopoulos, Antonios
Abstract : The United States and other actors such as the European Union impose "targeted sanctions" against foreign officials for acts carried out in their official capacity, or against legal entities of targeted states. This mirrors the practice and experience of the United Nations. The Security Council's practice of imposing comprehensive sanctions in the early 1990s quickly evolved into a practice of "targeted" or "smart" sanctions, to both improve effectiveness and to alleviate the significant effects of sanctions on the population of targeted states. However, the legal regime for resorting to sanctions is different when it comes to states acting unilaterally than it is for collective action within the framework of the UN Charter. This essay first clarifies some terminological issues. It then delves into the legality of the practice of unilateral "targeted sanctions, " and concludes that the most legally difficult aspect of these measures is their purported extraterritoriality.